Adrenal Weight In Relation To Duration of Pregnancy and Paunched Body Weight in The Indian Gerbil, Tatera Indica Indlca Hardwicke - Jain, A P (Annals of Arid Zone, 2016)
The' weights of adrenal- glands in the Indian gerbil, TateraÂ· indica indica, Hardwicke are significant1y correlated (P>.01) with the paunched body weight. There is no: correlation between paired adrenal weight and the crown-rum length of the embryos, which is indicative of the duration of, pregnancy. Results indicate that neither pregnancy nor the progress of pregnancy influence the weight of adrenal glands